2018
DOI: 10.1089/cap.2017.0072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metformin on Spatial and Verbal Memory in Children with ASD and Overweight Associated with Atypical Antipsychotic Use

Abstract: Objectives: Studies in humans and rodents suggest that metformin, a medicine typically used to treat type 2 diabetes, may have beneficial effects on memory. We sought to determine whether metformin improved spatial or verbal memory in children with autism spectrum disorder (ASD) and overweight associated with atypical antipsychotic use.Methods: We studied the effects of metformin (Riomet®) concentrate on spatial and verbal memory in 51 youth with ASD, ages 6 through 17 years, who were taking atypical antipsych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Similar salubrious metabolic effects of metformin were observed in ASD children and adolescent patients treated with antipsychotics (65,66). Another study showed that metformin failed to improve memory in overweight youth with ASD who were treated with atypical antipsychotic medication, but due to the small sample size and challenges the study encountered with regard to evaluation of cognitive functioning and irritable behavior in the tested ASD persons, additional studies are necessary to confirm the conclusions (67). Recently, metformin was reported to rebalance early neuronal network alterations and to reverse behavioral aberrations in a mouse model for Huntington's disease (68).…”
Section: Metformin Treatments In Neurological Disordersmentioning
confidence: 71%
“…Similar salubrious metabolic effects of metformin were observed in ASD children and adolescent patients treated with antipsychotics (65,66). Another study showed that metformin failed to improve memory in overweight youth with ASD who were treated with atypical antipsychotic medication, but due to the small sample size and challenges the study encountered with regard to evaluation of cognitive functioning and irritable behavior in the tested ASD persons, additional studies are necessary to confirm the conclusions (67). Recently, metformin was reported to rebalance early neuronal network alterations and to reverse behavioral aberrations in a mouse model for Huntington's disease (68).…”
Section: Metformin Treatments In Neurological Disordersmentioning
confidence: 71%
“…In a recent review summarizing the effectiveness of the selective serotonin reuptake inhibitor (SSRI) fluoxetine in ASD, it was concluded that fluoxetine may be effective in treating repetitive behaviors and irritability, while dose titrating triggers impulsive behavior, hyperactivity, irritability, and sleep disturbance ( Launay et al, 1987 ). While it has been suggested that the anti-diabetic drug metformin may have procognitive effects ( Ying et al, 2014 ), a study in ASD investigating the effects of metformin on memory function did not show any beneficial effects, and while no memory measures differed significantly between participants randomized to metformin versus placebo, the metformin group showed less improvement in verbal learning compared to the placebo group ( Aman et al, 2018 ). Sumatriptan is a 5HT 1B/D receptor agonist commonly used to treat migraine attacks ( Tfelt-Hansen and Hougaard, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, others suggested such an approach even without our data basis. Bradstreet et al proposed spironolactone for autistic disorders, and metformin was considered in the treatment of autistic disorders and for depression an involvement of the CRH–ACTH system was implied (Gold 2015 ; Checkley 1996 ; Bradstreet et al 2006 ; Wink et al 2017 ; Aman et al 2018 ). Given the safety profile for both metformin and spironolactone, a clinical approach might be feasible in human studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, substances affecting androgens, glucocorticoids, and mineralocorticoids have been considered as treatment options for disorders such as autism, depression, or PTSD (Bradstreet et al 2006 ; Wink et al 2017 ; Aman et al 2018 ). However, antagonists of hormones produced by the adrenal gland are rarely considered as potential treatment of disorders with social avoidance, and the respective impact of molecules with inhibitory action on androgens, glucocorticoids, and mineralocorticoids have not been conclusively studied.…”
Section: Introductionmentioning
confidence: 99%